A new paradigm to induce mental stress: the Sing-a-Song Stress Test (SSST) - Brouwer, Anne-Marie; Hogervorst, Maarten A. (Frontiers in Neuroscience, 2014)
We here introduce a new experimental paradigm to induce mental stress in a quick and easy way while adhering to ethical standards and controlling for potential confounds resulting from sensory input and body movements. In our Sing-a-Song Stress Test, participants are presented with neutral messages on a screen, interleaved with 1-min time intervals. The final message is that the participant should sing a song aloud after the interval has elapsed. Participants sit still during the whole procedure. We found that heart rate and skin conductance during the 1-min intervals following the sing-a-song stress message are substantially higher than during intervals following neutral messages. The order of magnitude of the rise is comparable to that achieved by the Trier Social Stress Test. Skin conductance increase correlates positively with experienced stress level as reported by participants. We also simulated stress detection in real time. When using both skin conductance and heart rate, stress is detected for 18 out of 20 participants, approximately 10 s after onset of the sing-a-song message. In conclusion, the Sing-a-Song Stress Test provides a quick, easy, controlled and potent way to induce mental stress and could be helpful in studies ranging from examining physiological effects of mental stress to evaluating interventions to reduce stress.